ગણિત, ધોરણ-પહેલું - (:unkn) unknown (Maharashtra State Bureau of Textbook Production & Curriculum Research, 2013)
The book is a Gujarati medium Mathematic textbook for class-1.
Mathematics, Class 1
Keywords: Gujarati; cગણિત; ધોરણ-પહેલું; Mathematics; Class 1; Mathematics; Gujarati; Gujarati